(untitled) (REMUNOM, 2025)
The advancement of mobile telephony has transformed consumer relations, placing users in an environment of complex contracts and algorithmic surveillance. This study investigates the level of awareness and vulnerability of consumers in the municipality of Campo Novo do Parecis-MT, a rapidly expanding agricultural hub. The central objective was to analyze whether classic socioeconomic indicators—education and income—act as protective factors against misinformation. This is a quantitative descriptive research conducted via a survey with a sample of 402 inhabitants. Data were subjected to Pearson’s Chi-square (x²) and Cramer’s V tests. The results reveal a scenario of "digital hypervulnerability": there was no statistically significant association between education level (p=0.11) or family income (p=0.25) and knowledge of consumer rights, indicating a phenomenon of "functional consumer illiteracy" that affects even the local intellectual elite. However, the age variable proved to be determinant (p=0.003), identifying young "digital natives" as the most vulnerable group. It is concluded that digital inclusion in the municipality has not been accompanied by legal literacy, demanding public consumer education policies that go beyond an assistentialist bias.